2012
DOI: 10.1002/biof.196
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids for treatment of Alzheimer's disease

Abstract: Retinoids are Vitamin A derivatives involved in cellular regulatory processes including cell differentiation, neurite outgrowth and defense against oxidative stress. Retinoids may also influence Amyloid beta processing upregulation of alpha secretase via ADAM10. Vitamin A and other retinoids also directly inhibit formation of Amyloid fibrils in vivo. These properties of retinoids are relevant to theories of Alzheimer's disease pathogenesis. Retinoids are already used in treatment of acne vulgaris, psoriasis, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
(86 reference statements)
1
30
0
2
Order By: Relevance
“…These effects were largely reversed by the administration of RA (29,30). Taken together, these data provide strong rationale investigating RA-based therapy in AD (31)(32)(33)(34).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…These effects were largely reversed by the administration of RA (29,30). Taken together, these data provide strong rationale investigating RA-based therapy in AD (31)(32)(33)(34).…”
mentioning
confidence: 67%
“…To test our hypothesis, we examined the expression of BACE1 in atRA-treated Tg2576, high fat diet, and LPS-challenged mice. These conditions have all been reported to induce inflammatory events in the brain (34,37,38). We further investigated the underlying molecular mechanism using in vitro cultured rat primary neurons.…”
mentioning
confidence: 99%
“…It also modulates neurogenesis, neuronal survival and synaptic plasticity in hippocampus, olfactory bulb and hypothalamus (61). Retinoids can regulate cell differentiation, neurite outgrowth and protection against oxidative stress (62). Several studies suggest vitamin A as a possible therapeutic agent in Alzheimer disease (AD): (i) the disruption of retinoid signaling induced deposition of Aβ in the cerebral blood vessels (63); (ii) vitamin A inhibited amyloid fibril formation (64) and (iii) in vivo studies revealed that administration of vitamin A decreased Aβ deposition and improved spatial learning and memory (65).…”
Section: Transport Of Retinolmentioning
confidence: 99%
“…Retinoic acids (RAs) are bioactive metabolites of retinoids (vitamin A derivatives) [27] that regulate a wide range of biological processes, including vision, cellular proliferation, differentiation, and embryogenesis [28,29]. RAs have been traditionally considered to be antioxidant compounds [30] and have attracted the attention of researchers because of their additional anti-inflammatory and immunomodulatory functions [31].…”
Section: Introductionmentioning
confidence: 99%